2021
DOI: 10.1128/spectrum.01123-21
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Diverse Toxin Complex Clusters and an eCIS Variant in Serratia proteamaculans Pathovars of the New Zealand Grass Grub ( Costelytra Giveni ) and Manuka Beetle ( Pyronota Spp.) Larvae

Abstract: New pathotypes of the insect pathogen Serratia , each with differing virulence attributes and host specificity toward larvae of the New Zealand manuka beetle and grass grub, have been identified. All of the Serratia proteamaculans isolates contained one of seven different insect-active toxin clusters or one of three eCIS variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…Direct nucleotide sequence comparison of the tcC components is hindered by several Tcs encoding for two TcC components and some, such as the S. proteamaculans D1.p1, Sm1a.p2, p1457, pD, p336, p1770, p1769, and p299, lack the tcC altogether. Additionally, the 3′ region of the tcC genes is highly divergent (Hurst et al, 2021 ). Higher variation in the tc clusters may be a result of selective host or environmental pressure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Direct nucleotide sequence comparison of the tcC components is hindered by several Tcs encoding for two TcC components and some, such as the S. proteamaculans D1.p1, Sm1a.p2, p1457, pD, p336, p1770, p1769, and p299, lack the tcC altogether. Additionally, the 3′ region of the tcC genes is highly divergent (Hurst et al, 2021 ). Higher variation in the tc clusters may be a result of selective host or environmental pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Gray shade denotes non‐ Serratia transmissible adaptive mega‐plasmids (STAMPs); blue Serratia entomophila ; pink Serratia proteamaculans ; yellow Yersinia frederiksenii . The right column denotes the different TcA clusters (Hurst et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the earliest studies of ABC toxins identified that the TcA component was involved in membrane binding and establishing host specificity [ 8 , 27 , 28 ]. With the determination of the first high-resolution structures, it was proposed that differences in specificity could be attributed to the variable incorporation of Ig-like domains into the TcA shell, identified at the time as putative receptor-binding domains ( Figure 2 ) [ 19 ].…”
Section: Host Cell Recognitionmentioning
confidence: 99%